The relationship between rural to urban migration in China and risk of depression in later life: An investigation of life course effects. (February 2021) - Zhang, Nan; Nazroo, James; Vanhoutte, Bram
Abstract: Background: Migrating between rural and urban areas over the life course profoundly shapes the conditions of later life. In the Chinese context, living in urban areas with an urban Hukou is associated with socioeconomic advantage. This study attempts to investigate how migration into urban areas in China is related to these processes and the association with risk of depression in later life by focusing on the timing and the type of migration (rural-urban residential mobility and/or institutional transition of Hukou status). Methods: We use sequence analysis to identify migration trajectories in the China Health and Retirement Longitudinal Study. Then we estimate how and why these trajectories are associated with risk of depression at older ages using a random intercept hierarchical linear model, distinguishing between three levels: city, household and individual. Results: The type of migration path taken over the life course is differentially associated with mental wellbeing in later life in China. Urban migration with rural-urban Hukou conversion during young adulthood is associated with lower levels of depression in later life. Urban migration at older ages regardless of Hukou transitions is protective against depression in old age. Formal social protection, particularly having a private pension, contributes substantially to the mental health advantage of social groups with an urban Hukou. Informal social mechanisms such as familial support are relevant, but only explain a small part of the differences in mental health. Conclusion: Having an urban Hukou has an independent protective role in shaping mental wellbeing in later life in China, potentially in part due to the entitlement to a private pension attached to this status. With weakening informal support in contemporary China, enhanced formal social protections in the form of adequate pensions should be put in place to mitigate structural inequalities associated with migration in old age. Highlights: The type and timing of migration matter for mental wellbeing in later life in China. Urban migration at older ages benefits more mentally than that earlier in life. Having an urban Hukou benefits mental wellbeing in later life. Having private pensions contributes to the mental health advantage of urban elderly.